Validation of the scale for evaluation of environment perception for physical activity practice in adults living in region of low socioeconomic level - Alex Antonio Florindo; Vanessa Valente Guimarães; José Cazuza de Farias Júnior; Emanuel Péricles Salvador; Thiago Herick De Sá; Rodrigo Siqueira Reis; Pedro Curi Hallal (Universidade Federal de Santa Catarina, 2012)
The objective of this study was to verify the validity of the perception of environment scale for engagement in physical activity in adult population. Two samples were drawn: the first, to compare the scale results with built environment and engagement in physical activity (767 individuals with 18 years or more); and the latter, for the analyses of repeatability (30 individuals with 60 years or more). Both studies were carried out in Ermelino Matarazzo District, eastern zone of the city of São Paulo. The perception of environment scale was developed based on the NEWS scale and on a social support for physical activity scale, and the final version comprised 38 questions. Data analysis: The scale results were compared to built environment and physical activity level, and for repeatability measure. The correlation coefficients for questions varied from r=0.51 to r=0.89, and for scores they varied from r=0.72 to r=0.94. There was significant agreement between means of perception of environment score of facilities for physical activity and the respective classification of built environment (p<0.001). The individuals who had any engagement in leisure-time physical activities had higher means for the scores of facilities (p<0.001), safe perception (p=0.033), and social support (p=0.001). The scale provided reliable and valid results for assessing the perception of environment for physical activity, mainly for the perception of the facilities of the environment.